Experiencias en torno a la integración social y de la salud vividas por mujeres inmigrantes brasileñas y africanas en Portugal : Cristianne Maria Famer Rocha [y otros tres] ; traducción del portugués de Fátima Andreu - Famer Rocha, Cristianne Maria (El Colegio de México, 2014)
Migratory movements have been increasingly the subject of analyzes from different perspectives in contemporary times. In this paper, we present the results of a survey of Brazilian and African women, living in Portugal, concerning their integration in the country and the conditions of their sexual and reproductive health, considering the status of migrants. The aim is to present some reflections on the health conditions of migrants, from the perspective of the social sciences and, in particular, women who were subjects of research. Therefore, focus groups were organized in Portugal with Brazilian and African migrant women and, from these, there were important evidence related to the topics mentioned. These testimonials are part of the body of the text and indicate relevant issues and worrying about the complexity and the impacts that involve migratory movements.